Silenciamiento de posibles genes antivirales en litopenaeus vannamei y su efecto en la susceptibilidad al virus del síndrome de la mancha blanca (wssv) - Mirabá, M. (2011)
In this study, the antiviral roles of 54 candidate genes from Litopenaeus vannamei, was evaluated. An experimental infection system was used, to assess the susceptibility to WSSV of shrimp where each one of the 54 candidate genes was knocked down by means of RNAi. For 41% of genes (22 genes) high levels of mortality were observed as a result of their silencing, independently of whether the animals were experimentally infected with WSSV, and thus their possible roles in the antiviral response could not be determined. Among the remaining 59% of genes, a phenotype of interest was observed for only one gene, whose silencing resulted in significant protection from the lethality of WSSV infection. We propose based on these data that this gene, which seems to encode a putative protease, may participate in regulating the life cycle and/or the pathogenicity of WSSV. Future studies will be needed to verify the phenotypes observed in this study, and especially to determine the possible roles of the gene identified here as a putative protease in regulating the WSSV-host interaction.